Hybrid 2D [Pb(CH3NH2)I2]n coordination polymer precursor for scalable perovskite deposition - Febriansyah, Benny (2020)
A two-dimensional hybrid coordination polymer [Pb(CH3NH2)I2]n featuring a well-defined layered structure is reported for scalable perovskite ink and deposition. This coordination polymer exhibits structural, spectroscopic, and physicochemical properties distinct from common PbI2 perovskite precursors. Notably, it serves as a methylamine “gas carrier” capable of liberating methylamine (CH3NH2) into the precursor solution, thus improving the solubility of perovskite in unconventional, greener processing solvents, such as acetonitrile. The purity of [Pb(CH3NH2)I2]n single crystals and the ability of the precursor to reduce sources of defects such as polyiodide species in solution allow the formation of high quality perovskite films. This eventually results in efficient and stable devices, fabricated via single step anti-solvent-free deposition method, transferable to large-area slot die coating. Gram scale synthesis of this unique lead precursor is demonstrated, essential for the scale-up of perovskite photovoltaic technology.